2022
DOI: 10.3390/biomedicines10020401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Novel Selective Peroxisome Proliferator-Activated Receptor α Modulator, Pemafibrate, on Metabolic Parameters: A Retrospective Longitudinal Study

Abstract: The modulation of peroxisome proliferator-activated receptors (PPARs), the superfamily of steroid–thyroid–retinoid nuclear receptors, is expected to induce an amazing crosstalk between energy-demanding organs. Here, we aimed to study the effects of the novel selective PPARα modulator, pemafibrate, on metabolic parameters in patients with dyslipidemia. We retrospectively studied patients who had taken pemafibrate and compared metabolic parameters at baseline with the data at 3, 6 and 12 months after the start o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…We also found serum lipids, such as TG and HDL-C, to be significantly improved when NAFLD patients were treated with pemafibrate. These results are consistent with previous reports ( 14 16 ) ( 11 , 17 21 ). Notably, the change in liver enzymes was accompanied with a significant improvement in liver stiffness, as measured by SWE.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We also found serum lipids, such as TG and HDL-C, to be significantly improved when NAFLD patients were treated with pemafibrate. These results are consistent with previous reports ( 14 16 ) ( 11 , 17 21 ). Notably, the change in liver enzymes was accompanied with a significant improvement in liver stiffness, as measured by SWE.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, pemafibrate improved liver fibrosis by reducing collagen 1α1 mRNA levels along with a decrease in the levels of pro-inflammatory mRNA ( 12 ). Indeed, pemafibrate induced a significant reduction in alanine aminotransferase (ALT) and γ-glutamyl transpeptidase (γ-GTP) levels in NAFLD patients ( 11 , 14 21 ). However, the efficacy of pemafibrate with respect to NAFLD was not addressed in these earlier studies due to cohort size.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a significant reduction in TG and non‐HDL‐C and an increase in HDL‐C were observed following pemafibrate treatment. These results are consistent with those of previous reports 33,34 . Recent studies have reported a significant decrease in the FAST score following pemafibrate treatment 16,19,35 and its correlation with the changes in ALT 16 or GGT levels 35 .…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those of previous reports. 33,34 Recent studies have reported a significant decrease in the FAST score following pemafibrate treatment 16,19,35 and its correlation with the changes in ALT 16 or GGT levels. 35 In this study, we found a significant reduction in the MAST score following pemafibrate treatment and a correlation between the reduction of the MAST score and the changes in ALT and GGT levels.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective longitudinal study indicates that pemafibrate significantly reduces plasma TG by 43.8% and increases HDL-C by 10.8% in patients with dyslipidemia after 3 months treatment. Furthermore, this molecule improves liver function and serum levels of uric acid and hemoglobin A1c ( Yanai et al, 2022 ).…”
Section: Strategies For Treatment Of Hypertriglyceridemiamentioning
confidence: 99%